Factors Contributing to Teachers’ Resistence in Integrating ICT in EFL Classroom in Senior High School - Nur Kamilah, Mirjam Anugerahwati (ELLITE, 2017)
ICT has become powerful media for teaching English, especially in improving students’ learning autonomy. However, studies have revealed that English teachers are sometimes resistant to ICT integration in the class, in which the resistance fails the effective ICT integration. The purpose of this study is to explain English teachers’ resistance towards ICT integration in the class by presenting and the categories of the resistance. There were seven teachers from six different senior high schools investigated in this study. Using semi-guided interview, observation and documentation, the study yielded the findings. There were three categories of resistance found; extreme, moderate and zero resistance. The factors contributing to the resistance were coming from external and internal, such as the unwillingness to learn and use ICT, lack of ICT competence and pedagogical knowledge, concerns about ICT for students, and unsupportive school facilities. It was also found that age might not matter much in contributing to the resistance and that the teachers’ perception is not always reflected in their teaching practice.Keywords: ICT integration, teacher’s resistance, factors of resistance, category of resistance.